2012
DOI: 10.1007/s10143-012-0407-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant intracranial aneurysms: morphology and clinical presentation

Abstract: The purpose of this study was to correlate the morphology of giant intracranial aneurysms (GIA) with their clinical presentation. Eighty patients with GIA, 14 males and 66 females, were studied. Univariate and multivariate analyses were made to test the associations between morphological and clinical features. The main locations of the unruptured GIA included the carotid cavernous segment, and for the ruptured GIA, the most frequent were the carotid supraclinoid and middle cerebral arteries. There was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…GCAs in the cavernous ICA usually have a benign natural course, but the rupture risk of a GCA is significantly higher in patients without thrombi or calcification 5)10)17). In the case presented here, the GCA was not accompanied by thrombi or calcification.…”
Section: Discussionmentioning
confidence: 99%
“…GCAs in the cavernous ICA usually have a benign natural course, but the rupture risk of a GCA is significantly higher in patients without thrombi or calcification 5)10)17). In the case presented here, the GCA was not accompanied by thrombi or calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Because most patients with GAs present with urgent clinical symptoms, 5 for most of these cases, 7T MR imaging examinations remain inaccessible. Considering the scarce opportunity to recruit patients with this extremely rare vascular disease, this study of GAs can help to further understand the complex pathophysiology of aneurysm formation, growth, and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intraluminal thrombus formation associated with repeated intramural hemorrhage and neovascularization in the wall seems to play an important role in GA growth. 4,5 Prior histopathologic studies of intracranial aneurysms have shown inflammation and associated iron deposits in the wall that correlated with growth and rupture of the aneurysm. 6,7 Previous MR imaging studies have revealed important morphologic features in these aneurysms, which are only partially assessable by DSA.…”
Section: 3mentioning
confidence: 99%
“…Although most common in the cavernous and supraclinoid internal carotid artery and the middle cerebral arteries, large intracranial aneurysms may originate anywhere with significant risk of rupture (Santos et al 2013). Large aneurysms can mimic tumors and cause clinical symptoms as a result of the mass effect despite endovascular or surgical treatment (Kim & Ko 2012).…”
Section: Discussionmentioning
confidence: 99%